Nonlinear optical behavior and optical power limiting characteristics of peripheral symmetrical and non-symmetrical zinc phthalocyanines with nanosecond pulsed excitation - GÖRK, GÜLŞEN; ERDEM, MURAT (PERGAMON-ELSEVIER SCIENCE LTD, 2021)
In this study, the optical nonlinear absorption and optical limiting performances of symmetrical and non-symmetrical zinc phthalocyanines in tetrahydrofuran (THF) solution were conducted by the open aperture z-scanning technique. A new non-symmetrically substituted metallophthalocyanine, namely 2(3)-[(4- nitrophenyl)ethynyl]-{9(10),16(17),23(24)-tris-(3,5-bis(trifluoromethyl)phenoxy)-phthalocyani-nato}zinc(II) (1b), was synthesized and then characterized by applying different spectroscopic methods, such as FT-IR, H-1 NMR and MALDI-TOF spectroscopy. According to the literature, {2(3),9(10),16(17),23(24)-tetrakis-(3,5-bis(trifluoromethyl)phenoxy)-phthalocyaninatolzin(II) (1a), {2,3,9,10,16,17,23,24-octakis-(3,5-bis(trifluomethyl)phenoxy)-phthalocyaninato}zinc(II) (2a) and 2(3)-[(4-nitrophenyl)ethynyl]-{9,10,16,17,23,24-hexakis-(3,5-bis(trifluoromethyl)phenoxy)-phthalocyani nato}zinc(II) (2b) were prepared. The effect of the symmetry and substituent's number on the nonlinear behavior was determined. A Nd:YAG laser, nanosecond pulsed at 532 nm, was used as the excitation source. The measurements of the input-output power and the nonlinear transmission properties were carried out for different excitation power values and different concentrations of the phthalocyanines in the THF solution. The nonlinear absorption coefficient of beta and the imaginary part of the third order nonlinear susceptibility of the medium (X-3) were found to be strongly dependent on the concentration. All the zinc phthalocyanine complexes showed good optical limiting performances, attributed to a reverse saturable absorption (RSA) process. The results indicate that the zinc phythcyanine complexes are promising candidates for optical limiting materials. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: Optical limiting; Nonlinear absorption; Symmetric phthalocyanines; Non-symmetric phthalocyanines